Non-native Mammals Are the Main Seed Dispersers of the Ancient Mediterranean Palm Chamaerops humilis L. in the Balearic Islands: Rescuers of a Lost Seed Dispersal Service? - Muñoz-Gallego, Raquel; Fedriani, José M.; Traveset, Anna (Frontiers in Ecology and Evolution, 2019)
Megafauna extinctions often lead to the disruption of plant-animal interactions, such as the seed-disperser mutualisms, which might entail severe consequences for plant populations and entire communities. Interestingly, the contemporary persistence of anachronistic plant species might be possible thanks to surrogate dispersers or seed dispersal “rescuers”. We know very little on how these relevant functional replacements are contributing to the performance of present-day plant-frugivore networks. The dwarf palm Chamaerops humilis L. is a Mediterranean endemism with fleshy fruits and typically dispersed by mammals. Despite its ecological importance and wide distribution in some of the Mediterranean islands, no information exists about its seed dispersal on these depauperated-fauna systems. In this study, we aim at identifying and quantifying the relative importance of introduced frugivores on the island of Mallorca (Balearic Islands), where no native terrestrial mammals exist. Specifically, we assess for the first time the seed dispersal effectiveness (SDE) for C. humilis on islands; we evaluate the quantitative component by fecal and regurgitation sampling surveys, and the qualitative component by means of seed germination experiments and seedling growth measures. Introduced goats (Capra hircus L.) and pine martens (Martes martes L.) were the local mammal fruit consumers of C. humilis identified in our study sites. Results suggest that goats are much more important quantitatively than pine martens, due to the high number of fruits handled in each foraging bout and their extremely high abundance on the island. However, pine marten-ingested seeds showed the highest final seedling emergence success and seedling growth, thus its qualitative contribution on C. humilis seed dispersal is higher than that of goats. Overall, SDE was almost 9-fold higher for goats than for pine martens. We conclude that these two non-native mammal species are effective seed dispersers of C. humilis in this and probably other Mediterranean islands, where humans led to the extinction of its native seed dispersers, as it was probably the case of the goat-like Myotragus balearicus in the Balearic Islands.